442 Reversible Cognitive Dysfunction and Neuropsychiatric Symptoms in Patients With Chiari Malformation Type I. (April 2023) - Henry, Luke; McDowell, Michael Maurice; Stephenson, Tina; Crittenden, J. Bret; Bird, Amy; Fernandez-de Thomas, Ricardo Jose; Strick, Peter; Friedlander, Robert Max
Abstract : INTRODUCTION: Chiari malformation type I (CMI) is a congenital/acquired structural condition where the cerebellar tonsils herniate through the foramen magnum, resulting in cerebellar and lower medulla/upper cervical spinal cord compression. Symptoms typically include occipital headaches, however, additional symptoms have been reported by symptomatic patients. We have observed a proportion reporting cognitive dysfunction and neuropsychiatric symptoms, which appear to improve following posterior fossa decompression (PFD). METHODS: Patients completed comprehensive neuropsychological evaluations, including a 90-minute standardized assessment of cognitive function across multiple domains and a self-reported assessment of neuropsychiatric symptoms, pre- and approximately 6-months post-surgery. RESULTS: This prospective study included patients with CMI who opted to undergo PFD surgery and reported cognitive or neuropsychiatric impairment between 2015 to 2021. All patients completed a comprehensive pre-operative neuropsychological assessment. A parallel assessment was completed at 6-month post-operative follow-up. 112 patients (Mage = 35.1 years; SD = 10.4) were included in pre-operative analyses, and of these, 31 patients (Mage = 32.5 years; SD = 10.5) were included in paired pre-post-operative analyses. Pre-operatively, CMI patients performed significantly worse than a standard norm on measures of executive function, attention, visuospatial memory, verbal memory, and neuropsychiatric symptoms. CONCLUSIONS: This is the first study to 1) demonstrate significant impairments in cognitive function and neuropsychiatric symptoms in CMI patients pre-operatively, and 2) show significant improvements in these domains at post-operative follow-up. This work calls attention to a significant proportion of CMI patients who suffer debilitating and life altering symptoms and provides compelling evidence for a role of the cerebellum in such conditions. In addition to CMI, cerebellar pathology should be considered as potential neuroanatomical site for patients with cognitive and neuropsychiatric impairment from other etiologies.